CRIMINAL RESPONSIBILITY OF PERPETRATORS WHO ADVERTISE ONLINE GAMBLING THROUGH INSTAGRAM (Decision Study No.98/Pid.Sus/2024/PN.Rta) - Subambhi, Sadam Ali (Inspiring Law Journal, 2025)
The development of technology in Indonesia is growing rapidly, this has also led to the development of online gambling crimes. Online gambling is a phenomenon that cannot be denied and is found in society, the increasing openness of online gambling sites has resulted in an increase in the number of online gambling players and online gambling advertising service providers in Indonesia. Online gambling advertising is an effort to advertise online gambling services provided through social media, one of which is Instagram. Advertising online gambling through Instagram has become the most strategic and effective in attracting public interest. Based on the results of the study, the formulation of the criminal offense of online gambling through Instagram can be charged with the ITE Law. In the Criminal Code, the crime of gambling is general (lex generalis) and the ITE Law Number 1 of 2024 regulates the crime of online gambling in Article 27 Paragraph (2) which is said to be a special regulation (lex specialis) of the Criminal Code. Actors who advertise online gambling via Instagram can be subject to criminal sanctions as regulated in Article 45 Paragraph (3) of the Republic of Indonesia Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning ITE, subject to a maximum imprisonment of 10 years and a maximum fine of IDR 10,000,000,000. can be held criminally responsible after fulfilling the elements of committing an unlawful act, being able to be responsible, having a form of error in the form of intent (dolus) and there is no justification and forgiveness. Based on the analysis of decision Number 98/Pid.Sus/2024/PN.Rta, it shows that there was an error made by the perpetrator by fulfilling the elements charged in accordance with Article 45 Paragraph (3) of Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning ITE.